Utilizing DMAIC method to optimize law enforcement official willingness to respond to disasters: an exploratory study. Issue 1 (16th September 2021) - Knezek, Erick B.; Vu, Thevu; Lee, Jim
Abstract : Purpose: The purpose of this case study is to develop a lean six sigma (LSS) define–measure–analyze–improve–control (DMAIC) procedure to optimize the willingness to respond (WTR) of Louisiana-based law enforcement officials (LEO) to disasters. Design/methodology/approach: Various LSS tools were used to implement DMAIC to clearly define the problem of WTR, measure the self-reported WTR through a survey, perform statistical analysis on the measured data to identify significant variables to WTR, brainstorm issues and improvements with stakeholders, develop mitigation strategies, implement a pilot solution survey and develop control measures. Findings: Louisiana LEO showed an average of 73.9% of WTR to all disasters. Seven significant variables influenced WTR, which are prior experience, transportation, duty to organization, risk to self, conflicting roles, training and incentive pay. The results from pilot solutions showed that utilizing incentive pay, adequate training and personal protective equipment (PPE) increased WTR from 0.5% up to 16%. Originality/value: This study developed and validated a unique procedure to improve LEO WTR to disasters, providing a set of DMAIC tools and concepts that can be used by other emergency response agencies. This research was performed during the COVID-19 pandemic and after Hurricane Laura impacted Louisiana.